دور حصة التلربية البدنية والرياضية في اكتساب المهاراات الاجتماعية لدى تلاميذ المرحلة الابتدائية من وجهة نظر الأستاذ - طالب, محمد شريف (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
تهدف الدراسة إلى إبراز دور حصة التربية البدنية و الرياضة في في إكتساب المهارات الإجتماعية لدى تلاميذ المرحلة الإبتدائية و ذلك من وجهة نظر الأساتذة، الغرض من الدراسة معرفة مدى دور حصة التربية البدنية و الرياضة في إكتساب المهارات الإجتماعية لدى تلاميذ المرحلة الإبتدائية. فالعينة: اشتملت على أساتذة ابتدائيات المقاطعة الاولى مستغانم المختارين بشكل عشوائي ( 63 أستاذ ) وقد استخدمنا أداة الاستبيان التي تتضمن مجموعة من الأسئلة و توصانا لأهم الاستنتاجات حيث أثبتت الدراسة أن لحصة التربية البدنية و الرياضية دور في اكتساب بعض المهارات الاجتماعية لدى تلاميذ المرحلة الابتدائية من وجهة نظر الأساتذة ، كما تساهم في تنمية روح المسؤولية والتعاون. وهذا أدى بنا للخروج بأهم الاقتراحات ألا وهي الاعتماد على أساليب التدريس الحديثة في حصص التربية البدنية كنشاط رياضي، نظرًا لأنها تسهم بشكل كبير في تعزيز التعاون والتواصل للتلاميذ. // // // // // // Title: The role of the physicaleducation and sports class in acquiring social skillsamongelementaryschoolstudentsfrom the teachers’ point of view. Abstract The purpose of the study: to determine the extent of the role of the physical education and sports class in the acquisition of social skills among elementary school students. The sample: included randomly selected elementary school teachers in Mostaganem Province (63 teachers). we used: The research included the use of a questionnaire technique that includes a set of questions. And we discovered most important conclusions: The study demonstrated that the physical education and sports class has a role in the acquisition of some social skills among elementary school students from the point of view of teachers, as well as the emergence of social integration, increased self-confidence and emotional control, and the role of physical and sports activities in developing the spirit of responsibility and cooperation. It also contributes the most important suggestions: Relying on modern teaching methods in physical education classes as a sporting activity, as they contribute greatly to enhancing cooperation and communication for students.
LEPS-2024-6
Keywords: التربية البدنية و الرياضة- الطفولة- المهارات الاجتماعية // // physical education and sports class – childhood- social skills